Decreased antimicrobial prescribing rate following academic detailing of resident physicians in outpatient clinic - Shannon L. Andrews; Amy A. Gravely; Amanda Beaudoin; Meghan K. Rothenberger; Dimitri M. Drekonja (Cambridge University Press, 2023)
Among 37 internal-medicine resident physicians assigned to our outpatient clinic at Minneapolis Veterans' Affairs Health Care System (MVAHCS) on July 1, 2017, we designed a pre- and postintervention observational study. Our results show that in-person academic detailing around outpatient antimicrobial selection was associated with a decrease in outpatient antimicrobial prescriptions in a group of high-prescribing resident physicians.